STUDYING THE CAUSES OF CAVERNOUS SINUS THROMBOSIS AT COVID-19 - Yakubova, M.M.; Rakhmatullaeva, G.Q.; Mirzaeva, K.S.; Said-Akhmedova, S.K.; Ikromova, M.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. Currently, complications developing in patients with COVID-19 are a serious health problem worldwide. Purpose of the study: to study the causes of thrombosis of cavernous sinus in patients with COVID-19 Material and methods. 147 patients with cavernous sinus thrombosis (TCS) and Covid-19 were investigated. Of these, 88 (61%) are men and 59 (39%) are women. Methods of Examination: clinical-neurological, general clinical and biochemical research, MRI/MSCT of the brain. Statistical analysis was carried out in Microsoft Excel 2010, descriptive statistics. Results. The age of patients with TCS ranged from 22 to 81 years (average age 54.97±0.93), more often at the age of 40–70 years (80%). Men were more often ill between the ages of 41 and 60 years (59%) (average age 51.68±1.17), and women from 51 to 70 years (75%) (average age - 60.22±1,25). Before Covid-19, 73% of patients suffered from diabetes. The first clinical signs of COVID-19 were increasing body temperature (90%) and the violation of smell and taste (89%). The TCS developed in patients on average after 21.40±1.54 days after detection of COVID-19. However, in women, it begins earlier (an average of 18.56±2.12 days) than in men (an average of 23.37±2.13 days). Conclusions. TCS at COVID-19 was more often observed (80%) aged 40–70 years (cf. age - 54.97 ± 0.93). TCS is more often found in the average age group in men, however in women medium and elderly age group. Diabetes mellitus may be a risk factor for the development of TCS. The first clinical signs of COVID-19, in patients of the TCS, were increasing the body temperature (90%), and the violation of smell and taste (89%). TCS develop on average after 21.40±1.54 days, after the detection of COVID-19.